The assessment of bone strength based on the results of ultrasound densitometry in infants born after in vitro fertilization (IVF) weighing less than 1500 g - D.R. Merzlyakova; N.R. Khafizova; G.A. Vakhitova; Z.A. Shangareeva; G.G. Gilyazova; A.I. Nazarova (LCC «Medicine-Inform», 2023)
D.R. Merzlyakova1,2, N.R. Hafizova1, G.A. Vakhitova1, Z.A. Shangareeva1, G.G. Gilyazova2, A.I. Nazarova1 1Bashkir State Medical University, Ufa, Russian Federation 2Republican Children's Clinical Hospital, Ufa, Russian Federation Aim: to assess the status of bone mineral density (BMD) using the ultrasound densitometry as a screening technique in premature in vitro fertilization (IVF) and non-IVF infants weighing less than 1500 g at birth. Patients and Methods: the study included 189 premature babies who stayed in the department for newborns and premature infants with health problems. The infants were divided into two groups, depending on the IVF use: born through the IVF or conceived naturally. Each of the groups was divided into two subgroups based on the infant weight at birth: subgroups A consisted of very low birth weight (VLBW) babies and subgroups B consisted of extremely low birth weight (ELBW) babies. The first group (n=101) consisted of IVF-infants, 52 and 49 of them were included in subgroups 1A and 1B, respectively. The second group (comparison, n=88) consisted of the naturally conceived infants, 46 and 42 of them were included in subgroups 2A and 2B, respectively. BMD was measured using the ultrasound densitometry method. The evaluated parameters comprised the speed of sound (SOS) and Z-score, representing the difference in BMD between the studied infants and the mean BMD of other children of the same age and gender (standard deviation (SD) for the tibia). Z-score <-1 SD (SOS <10‰ and >3‰) was associated with a low bone density and Z-score <-2 SD (SOS <3‰) - with a clinically significant low bone density. Results: the normal values of bone density were found in 39 (38.6%) infants of group 1 and 58 (65.9%) infants of group 2 (p>0.05). In the group 1 infants a decrease in bone density was found more frequently than in the group 2 infants: 49 (48.5%) and 21 (23.8%), respectively, p<0.05, and the difference was statistically significant (<-1SD). A clinically significant low bone density (SOS <3‰) found in 13 (12.8%) IVF-babies. The extremely low birth weight (ELBW) in IVF-babies is a risk factor for osteopenia and osteoporosis. Conclusion: a significant decrease in the bone density values (SOS <10‰ and >3‰) was found in IVF-infants as compared to those in naturally conceived infants. A clinically significant decrease in bone density in premature IVF-infants with ELBW was reported in 12.8% of cases. The early diagnosis of osteopenia can be established by using a safe technique - the ultrasound densitometry. Keywords: bone mineral density, densitometry, in vitro fertilization, IVF, premature babies, osteopenia, bone tissue, screening, very low birth weight, extremely low birth weight. For citation: Merzlyakova D.R., Hafizova N.R., Vakhitova G.A. et al. The assessment of bone strength based on the results of ultrasound densitometry in infants born after in vitro fertilization (IVF) weighing less than 1500 g. Russian Journal of Woman and Child Health. 2023;6(1):34-38 (in Russ.). DOI: 10.32364/2618-8430-2023-6-1-34-38.